Strategi dan Praktik Manajemen Perbankan Syariah - Afif Fathanah Radiyyah; Nuri Aslami (JIKEM: Jurnal Ilmu Komputer, Ekonomi dan Manajemen, 2022)
Islamic banks must function as a means to collect public savings and develop them. The point is that Islamic banks are institutions that function to invest public funds in accordance with Islamic recommendations effectively, productively and for the benefit of Muslims. The main objective of implementing Islamic banking, which is to unite Muslims, restore the strength, vitality, role and position of Islam on this earth can be achieved.